Psychometric properties of Torga version of the Stroop Test - Garcia, Inês Queiroz (2016)
Background & Goals: A new Portuguese version of the Stroop Test is essential for the neuropsychological assessment. The previous Portuguese version included colors that many people could not distinguish. Thus, it is aimed to describe the psychometric properties of a new version, called the Torga version of the Stroop Test in a sample of the Portuguese population. Methods: Being part of the Estudos Normativos de Instrumentos Neuropsicológicos/ Normative Studies of Neuropsychological Instruments, this research has a global sample of 544 subjects (241 men and 303 women) aged from 18 to 97 years. The assessment included the Torga version of the Stroop Test, the Rey-Osterrieth Complex Figure, and the Frontal Battey Assessment, used as measures of executive functions. Results: The Torga version of the Stroop Test showed very good internal consistency (Cronbach's α = 0.99). It also revealed adequate temporal stability and convergent validity. Conclusion: The Torga version of the Stroop Test appears to be an adequate instrument for the neuropsychological assessment of Portuguese adults. Considering the importance of this test in the context of neuropsychological assessment, more studies with new samples, including clinical samples are encouraged.